Lead‐Free Solar Cells based on Tin Halide Perovskite Films with High Coverage and Improved Aggregation. (5th September 2018) - Liu, Jiewei; Ozaki, Masashi; Yakumaru, Shinya; Handa, Taketo; Nishikubo, Ryosuke; Kanemitsu, Yoshihiko; Saeki, Akinori; Murata, Yasujiro; Murdey, Richard; Wakamiya, Atsushi
Abstract: Two simple methods to improve tin halide perovskite film structure are introduced, aimed at increasing the power conversion efficiency of lead free perovskite solar cells. First, a hot antisolvent treatment (HAT) was found to increase the film coverage and prevent electrical shunting in the photovoltaic device. Second, it was discovered that annealing under a low partial pressure of dimethyl sulfoxide vapor increased the average crystallite size. The topographical and electrical qualities of the perovskite films are substantively improved as a result of the combined treatments, facilitating the fabrication of tin‐based perovskite solar cell devices with power conversion efficiencies of over 7 %. Abstract : Zwei einfache Verfahren, die Behandlung mit heißem Antisolvens (HAT) und Solvensdampfbehandlung bei niedrigem Partialdruck, werden eingeführt, um den Herstellungsprozess von Zinnhalogenid‐Perowskitfilmen zu modifizieren. Diese Behandlungen verbessern die Filmqualität signifikant und steigern die photovoltaische Leistung von Zinn‐basierten Perowskit‐Solarzellen.